Preparation of a New Cd(II)-Imprinted Polymer and Its Application to Preconcentration and Determination of Cd(II) Ion from Aqueous Solution by SPE-FAAS - Teguh Wirawan; Ganden Supriyanto; Agoes Soegianto (Universitas Gadjah Mada, 2019)
A novel ion Imprinted polymer (IIP) material with 8-hydroxyquinoline (8HQ) (the complexing ligands), methacrylic acid (MAA) (the monomers), ethylene glycol dimethacrylate (EGDMA) (the crosslinker agent), benzoyl peroxide (the initiator), and ethanol-acetonitrile (2:1) (the porogen) as adsorbent for the determination of cadmium by solid phase extraction–flame atomic absorption spectrometry (SPE-FAAS) has been synthesized. Synthesis of IIP was done by precipitation polymerization method. The imprinted Cd(II) ions were removed by leaching method using 1 mol L-1 nitric acid. The IIP was characterized by fourier transform infra-red (FT-IR) spectroscopy and scanning electron microscopy (SEM) to ensure successful synthesis of IIP. The experimental parameters for SPE extraction, such as pH of the sample, loading rate, and elution rate, have been optimized. The optimum pH for quantitative Cd(II) retention was 6, and the elution was completed with 2 mL of 1.0 mol L-1 nitric acid. The optimum loading rate was 0.5 mL min-1. Under optimum conditions, the proposed method with theoretical enrichment factor 50 times has a detection limit of 0.5 µg L-1 and the recovery of 97.75%.